First record of Mikrosyphar zosterae (Chordariaceae, Phaeophyceae) in the southern hemisphere and as an endophyte in the brown algal genera Leathesia and Colpomenia - Martins, Nuno T.; Gurgel, Carlos Frederico D.; Spokes, Tracey M.; Cassano, Valéria (Phytotaxa, 2021)
Several filamentous endophytic genera are assigned to the Phaeophyceae, in particular to the family Chordariaceae (Cormaci et al. 2012). Brown endophytic filamentous algae are known to cause infections in host marine algae (Schoenrock et al. 2013; Ogandaga et al. 2016, 2017; Gao et al. 2019). Acting as pathogens, they may cause morphological, physiological and ecological changes in the host alga such as production of galls and wart-like spots, changes in metabolism and growth rates, and changes in survivorship and reproduction (Schoenrock et al. 2013; Ogandaga et al. 2016, 2017; Gao et al. 2019). Among brown algal filamentous endophytes, the genus Mikrosyphar Kuckuck is relatively understudied. To date, only Mikrosyphar zosterae Kuckuck (1895: 177) was studied thoroughly (Ogandaga et al. 2016, 2017).